2019
DOI: 10.2478/rtuect-2019-0078
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Energy Willow Plantations for Biological Reclamation of Soils Polluted by 137Cs and Heavy Metals, and for Control of Nutrients Leaking into Water Systems

Abstract: Willow is a low-maintenance crop that has potential for energy production and enhancing the local environment. The area of commercial plantations of willow in Europe is mostly concentrated in Sweden, with more than 20 000 ha. Willow trees are used not only for energy production, but also for reclamation of polluted soils because a plantation may grow for 20–25 years, with a three-year period of harvesting. Our research covers issues of reclamation of soils contaminated by radionuclides and heavy metals, and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…As a result, the ash had a positive effect on willow growing, especially in the second year after application (Table 3). In our experiment, the ash had a positive effect with dose application 1.0 and 1.5 mg dry mass ha -1 (Parka et al, 2005;Rodzkin et al, 2018;Rodzkin et al, 2019). Another study reported the positive effect of wood ash application on the soil acidity and the size of willow stems, but not on biomass production because the mean number of stems was significantly smaller in the ash-treated plots than in the control plots (Lazdina et al, 2011).…”
Section: Peat Ash Application On Ef2mentioning
confidence: 41%
“…As a result, the ash had a positive effect on willow growing, especially in the second year after application (Table 3). In our experiment, the ash had a positive effect with dose application 1.0 and 1.5 mg dry mass ha -1 (Parka et al, 2005;Rodzkin et al, 2018;Rodzkin et al, 2019). Another study reported the positive effect of wood ash application on the soil acidity and the size of willow stems, but not on biomass production because the mean number of stems was significantly smaller in the ash-treated plots than in the control plots (Lazdina et al, 2011).…”
Section: Peat Ash Application On Ef2mentioning
confidence: 41%
“…Raw wood composed mainly of cellulose and lignin contains C in the amount of approx. 50%, while N and P in raw wood are only about 1.0–1.5% and 0.15–0.20% respectively 32 . The C:N:P proportions depend to some extent on the wood species 31 .…”
Section: Discussionmentioning
confidence: 92%
“…and willows (Salix sp. ), are common phytoremediation and biorefinery crops on marginal lands (Brereton et al, 2017;Dimitriou and Aronsson, 2005;Gonzalez et al, 2018;Rodzkin and Volk, 2018;Sas et al, 2021;Volk et al, 2006), with high potential for growth on salinised soils. For example, some cultivars can maintain transpiration and growth under saline conditions up to 6-8 dS m -1 (Bilek et al, 2020;Chen and Polle, 2010;Huang et al, 2020;Jerbi et al, 2020;Mirck andZalesny, 2015, 2015;Steppuhn et al, 2008).…”
Section: Introductionmentioning
confidence: 99%